Effects of a Foot Pump on the Incidence of Deep Vein Thrombosis After Total Knee Arthroplasty in Patients Given Edoxaban: A Randomized Controlled Study. Issue 1 (January 2016) - Sakai, Tatsuya; Izumi, Masahiro; Kumagai, Kenji; Kidera, Kenichi; Yamaguchi, Takayuki; Asahara, Tomohiko; Kozuru, Hideko; Jiuchi, Yuka; Mawatari, Masaaki; Osaki, Makoto; Motokawa, Satoru; Migita, Kiyoshi
Abstract : Abstract: We conducted a randomized clinical trial to compare the effectiveness of the A-V Impulse System foot pump for reducing the incidence of deep-vein thrombosis (DVT) after total knee arthroplasty (TKA) in patients under edoxaban thromboprophylaxis. Patients undergoing primary TKA at our institution between September 2013 and March 2015 were enrolled after obtaining informed consent. The patients were randomized to use the foot pump (n = 58) and not to use the foot pump (n = 62). Both groups were given prophylactic edoxaban. Primary outcomes were any DVT as detected by bilateral ultrasonography up to postoperative day 10 (POD10) and pulmonary embolism (PE) up to POD28. The safety outcomes were bleeding and death of any cause up to POD28. Plasma D-dimer levels were measured before TKA and on POD10 after TKA. Immunoglobulin G (IgG)-class anti-PF4/heparin antibodies were measured using an IgG-specific enzyme-linked immunosorbent assay. The incidences of any DVT up to POD28 were 31.0% and 17.7% in patients with or without the foot pump, respectively. The incidences of major bleeding up to POD28 were 5.1% and 4.8% in patients with or without the foot pump, respectively. Foot pump use did not significantly reduce the incidence of DVTs in patients undergoing TKA under edoxaban thromboprophylaxis. Although seroconversion of anti-PF4/heparin antibodies was confirmed in one-fourth of patients, the seroconversion rates did not differ between patients with (20.7%) or without (25.8%) foot pump use. This study shows that the A-V Impulse system foot pump did not affect the incidence of DVT under edoxaban thromboprophylaxis in patients undergoing TKA. Seroconversion of anti-PF4/heparin antibodies was detected in a significant number of patients who underwent TKA under antithrombotic prophylaxis using edoxaban.